Disfuncionalidad del pensamiento y su influencia en la respuesta emocional de un adolescente en crisis - Rodriguez Vargas, Laura Lissette (2020)
This research presents a case study within the area of Clinical Psychology whose theme is the dysfunctionality of thinking and its influence on the emotional response of a 15-year-old adolescent, focused on the theory of Behavioral Cognitive Current originated from Aaron Beck. Psychometric tests such as the Ruiz and Lujan Automatic Thoughts Inventory are used as an instrument to obtain the required information on automatic thoughts classified within the framework of cognitive distortions and the Beck Depression Inventory to measure the patient's emotional response. In addition to the use of techniques such as clinical observation, clinical history and psychological evaluation in general, the fundamental objective is to determine the influence that dysfunctional thoughts exert on the emotional response of the patient of the Communal Center "Christ of consolation" of the city of Babahoyo - Province of the Rios.